Sero-Prevalence and Sero-Incidence of Antibodies to SARS-CoV-2 in Health Care Workers in Israel, Prior to Mass COVID-19 Vaccination - Muhsen, Khitam; Schwaber, Mitchell J.; Bishara, Jihad; Kassem, Eias; Atamna, Alaa; Na'amnih, Wasef; Goren, Sophy; Bialik, Anya; Mohsen, Jameel; Zaide, Yona; Hazan, Nimrod; Ariel-Cohen, Ortal; et al. (Frontiers in Medicine, 2021)
Objectives: This study aims to examine the prevalence and risk factors of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) sero-positivity in health care workers (HCWs), a main risk group, and assess the sero-incidence of SARS-CoV-2 infection between the first and second waves of coronavirus disease 2019 (COVID-19) in Israel. Methods: A longitudinal study was conducted among 874 HCWs from nine hospitals. Demographics, health information, and blood samples were obtained at baseline (first wave—April–May 2020) and at follow-up (n = 373) (second wave—September–November 2020). Sero-positivity was determined based on the detection of total antibodies to the nucleocapsid antigen of SARS-CoV-2, using electro-chemiluminescence immunoassay (Elecsys® Anti-SARS-CoV-2, Roche Diagnostics, Rotkreuz, Switzerland). Results: The sero-prevalence of SARS-CoV-2 antibodies was 1.1% [95% confidence intervals (CI) 0.6–2.1] at baseline and 8.3% (95% CI 5.9–11.6) at follow-up. The sero-conversion of SARS-CoV-2 serum antibody was 6.9% (95% CI 4.7–9.9) during the study period. The increase in SARS-CoV-2 sero-prevalence paralleled the rise in PCR-confirmed SARS-CoV-2 infections among the HCWs across the country. The likelihood of SARS-CoV-2 sero-prevalence was higher in males vs. females [odds ratio (OR) 2.52 (95% CI 1.05–6.06)] and in nurses vs. physicians [OR 4.26 (95% CI 1.08–16.77)] and was associated with being quarantined due to exposure to COVID-19 patients [OR 3.54 (95% CI 1.58–7.89)] and having a positive PCR result [OR 109.5 (95% CI 23.88–502.12)]. Conclusions: A significant increase in the risk of SARS-CoV-2 infection was found among HCWs between the first and second waves of COVID-19 in Israel. Nonetheless, the sero-prevalence of SARS-CoV-2 antibodies remains low, similar to the general population. Our findings reinforce the rigorous infection control policy, including quarantine, and utilization of personal protective equipment that should be continued together with COVID-19 immunization in HCWs and the general population.